The Effectiveness Of Clustering Essay Technique In Teaching Writing Viewed From Students’ Intelligence - Anita Budi Rahayu (Dharma Pendidikan, 2017)
This research is aimed at finding out: (1) whether or not Clustering essay Technique is more effective than conventional Technique in teaching writing; (2) whether the students who have high intelligence have better writing ability than those who have low intelligence; and (3) whether there is an interaction between teaching techniques and intelligence in teaching writing. This experimental research was carried out in SMAN I Berbek Nganjuk in the academic year of 2016/2017 from April to June 2017. The population was the eleventh grade students of in the academic year of 2016/2017, and the number of population was 168 students who were divided into four classes. The samples, which were selected by using cluster random sampling, were XI B as the experimental group and XI D as the control group. Each group consists of 42 students. The experimental group was treated by using Clustering essay Technique, while the control group was treated by using Conventional Technique. The data analysis shows the following findings: (1) Clustering essayTechnique is more effective than Conventional Technique in teaching writing; (2) students with high intelligence have better writing ability than those having low intelligence; and (3) there is an interaction between teaching techniques and intelligence in teaching writing.